EMG motion pattern classification through design and optimization of Neural Network - Md. Rezwanul, Ahsan; Muhammad Ibn, Ibrahimy; Othman Omran, Khalifa (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/